2001
DOI: 10.1179/joc.2001.13.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Calmette-Guerin Down-Regulates CD1b Induction by Granulocyte-Macrophage Colony Stimulating Factor in Human Peripheral Blood Monocytes

Abstract: Non-peptide antigens (e.g. glycolipids of microbial origin) presented by monocyte-associated CD1 molecules to T cells appear to play an important role in host immunity against tuberculosis and other pathogenic bacteria. Since vaccination with Bacillus Calmette-Guerin (BCG) has limited efficacy, the influence of viable BCG organisms on the induction of CD1b antigen by granulocyte macrophage-colony stimulating factor (GM-CSF) has been tested in adherent mononuclear cells obtained from peripheral blood of healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Preliminary studies performed in our laboratory showed that chemical inactivation of BCG with rifampin does not prevent the inhibitory effect of the microorganism on CD1b expression (28). Therefore, further experiments were carried out using either viable or heat-killed BCG (BCG-H) organisms.…”
Section: Influence Of Bcg On the Induction Of Group I Cd1 Molecules Bmentioning
confidence: 99%
“…Preliminary studies performed in our laboratory showed that chemical inactivation of BCG with rifampin does not prevent the inhibitory effect of the microorganism on CD1b expression (28). Therefore, further experiments were carried out using either viable or heat-killed BCG (BCG-H) organisms.…”
Section: Influence Of Bcg On the Induction Of Group I Cd1 Molecules Bmentioning
confidence: 99%
“…13,47 It has therefore been suggested that the unsatisfactory results in the treatment of tuberculosis obtained with BCG vaccination may be due to mycobacterium-induced impairment of the CD1 system. 48 Similar to the role of CD1 molecule down-regulation in the inefficient immune response toward mycobacteria, we hypothesized that CD1 down-regulation might play a role in escaping the immune system in melanoma, as tumor expressed gangliosides have been shown to be immunogenic but do not elicit a clinically effective immune response. 49 -52 When CD1 expression was analyzed in melanoma lesions, we found significantly higher CD1a, b, c, d expression in primary compared to metastatic lesions in situ (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in our laboratory [18,23] and elsewhere [24] showed that infection of human AMNC with BCG is able to restrain GM-CSF induced upregulation of CD1 molecules. However, we have demonstrated a limited CD1 induction in AMNC following in vitro exposure to BCG alone [18,23].…”
Section: Introductionmentioning
confidence: 98%